Actions of Agonists and Antagonists of the ghrelin/GHS-R Pathway on GH Secretion, Appetite, and cFos Activity - Hassouna, Rim; Labarthe, Alexandra; Zizzari, Philippe; Videau, Catherine; Culler, Michael D.; Epelbaum, Jacques; Tolle, Virginie (Frontiers in Endocrinology, 2013)
The stimulatory effects of ghrelin, a 28-AA acylated peptide originally isolated from stomach, on GH secretion and feeding are exclusively mediated through the growth hormone secretagogue 1a receptor (GHS-R1a), the only ghrelin receptor described so far. Several GHS-R1a agonists and antagonists have been developed to treat metabolic or nutritional disorders but their mechanisms of action in the central nervous system remain poorly understood. In the present study, we compared the activity of BIM-28163, a GHS-R1a antagonist and of several agonists, including native ghrelin and the potent synthetic agonist, BIM-28131, to modulate food intake, GH secretion and c-Fos activity in ArcN, NTS and AP in wild-type and NPY-GFP mice. BIM-28131 was as effective as ghrelin in stimulating GH secretion, but more active than ghrelin in inducing feeding. It stimulated cFos activity similarly to ghrelin in the NTS and AP but was more powerful in the ArcN, suggesting that the super-agonist activity of BIM-28131 is mostly mediated in the ArcN. BIM-28163 antagonized ghrelin-induced GH secretion but not ghrelin-induced food consumption and cFos activation, rather it stimulated food intake and cFos activity without affecting GH secretion. The level of cFos activation was dependent on the region considered: BIM-28163 was as active as ghrelin in the NTS, but less active in the ArcN and AP. All compounds also induced cFos immunoreactivity in ArcN NPY neurons but BIM-28131 was the most active. In conclusion, these data demonstrate that two peptide analogs of ghrelin, BIM-28163 and BIM-28131, are powerful stimulators of appetite in mice, acting through pathways and key brain regions involved in the control of appetite that are only partially superimposable from those activated by ghrelin. A better understanding of the molecular pathways activated by these compounds could be useful in devising future therapeutic applications, such as for cachexia and anorexia.